Fenología y dinámica poblacional de Artrópodos en el cultivo del Algodonero (Gossypíum Hirsutum) Variedad Upland Americano BJA - 594 en la región San Martín. - Díaz Vela, Pedro Miguel (2001)
The present research Work was carried out Determining and correlation the Dinamic populathion of Plagues and Beneficent to artrópodos, in the fenológíc whole stage of Cotton crops land, BJA-594 strain. This experiment was carried out in the property Santa Clara of property of Mrs. Etelbina Lozano Lozano; it was located in Juan Guerra War District, County of San Martín, Department of San Martín. The soil characteristic was franc texture, pH 8,22 and organic matter content of 3,95; the altitude land is 232 m.s.n.m with an precipitation average of 1208 mm/year. The out evaluations were made in an area of 2 500 m2 in the which were distribuite 5 parcels; from here it was evaluated 20 plants for each one of sub parcels from central part. The test of lineal correlation test was used to statistical analysis either to harmful insects as benefits end variables phonological. The biggest population of harmful arthropods that we founded corresponded to Coleopterous, Homopterous and Hemipterous, order and The benefit arthropod us belong to the Hemipterous, Coleopterous, Hymenoptera Araneae, Dipteral and Neuropterous respectibaly.